Karakterisasi Aktivitas Antioksidan Ekstrak Etanol Bawang Lanang (Allium sativum L.) Melalui Uji DPPH - Shinta Nursifa; Saeful Amin; Olivia Fauzi Syalamatul Syalamatul Putri; Firli Nimah Dinda Azqiah (Lembaga Pengembangan Kinerja Dosen, 2025)
Purpose: This study aimed to evaluate the antioxidant activity and identify secondary metabolite compounds of the ethanol extract from lanang onion bulbs (Allium sativum L.) against DPPH free radicals. Methodology/approach: Extraction was performed by maceration using 95% ethanol, followed by fractionation with n-hexane, ethyl acetate, and water. Antioxidant activity was tested qualitatively by thin-layer chromatography (TLC) and quantitatively by the DPPH method using a UV-Vis spectrophotometer. Phytochemical screening was carried out to identify bioactive compound content. Results/findings: The ethanol extract and ethyl acetate fraction exhibited strong antioxidant activity with IC₅₀ values of 13.85 ppm and 7.27 ppm, respectively. Phytochemical tests revealed the presence of flavonoids, saponins, alkaloids, tannins, steroids, and triterpenoids in each fraction. Limitations: This study was limited to in vitro testing and did not include comprehensive toxicity or in vivo analysis. Contribution: This research contributes to the development of natural antioxidants in pharmacology, phytochemistry, traditional medicine, and functional food industries. The results are useful for researchers, academics, and herbal or health-related industries.